2017
DOI: 10.1515/tjb-2016-0261
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase 1 (SOD 1) A251G Polymorphism

Abstract: Objective: A genetic polymorphism of SOD1 A251G(rs2070424) is in the 3rd intron region of the SOD gene. The aim of this study was to determine the frequencies of the polymorphisms of the SOD1 A251G in a Turkish population, including 494 healthy individuals. Methods: The 494 Turkish individuals were genotyped for polymorphisms of SOD1 gene. The distribution of SOD1 A251G polymorphisms in this population was examined using a PCR-RFLP method. Genotype and allele frequencies were estimated by counting. Hardy-Weinb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Interestingly, we found mainly variant AA (93.3%) in the PCOS women and only 4 (6.7%) patients with genotype AG, while there are not any patients with GG genotype. A study conducted by Silig et al [14] revealed that the frequencies of AA, AG and GG genotypes in a healthy Turkish population were found to be % 86.2, % 13.4 and % 0.4 respectively. It is possible that due to a small number of patients, we did not observe any cases of GG genotype.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, we found mainly variant AA (93.3%) in the PCOS women and only 4 (6.7%) patients with genotype AG, while there are not any patients with GG genotype. A study conducted by Silig et al [14] revealed that the frequencies of AA, AG and GG genotypes in a healthy Turkish population were found to be % 86.2, % 13.4 and % 0.4 respectively. It is possible that due to a small number of patients, we did not observe any cases of GG genotype.…”
Section: Discussionmentioning
confidence: 98%
“…The variability in SOD activity and the harmful consequences of oxidative stress may be also related to intra-individual differences, presumed to be associated with singlenucleotide polymorphisms (SNP) of SOD1. One of them could be rs2070424 (A251G) of the SOD1 gene, which is located in the 3rd intron of the SOD1 gene [14]. This polymorphism could be associated with increased body fat [15], impaired glucose regulation, type 2 diabetes [16] and inflammation [17], which are common disorders observed in the course of PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, smokers had lower serum SOD levels than non-smokers, but this was not statistically significant. This is important because it was the first study on SOD1 A251G polymorphism in the Turkish population (10) . We believe that research on antioxidant systems in different areas, such as our work, will provide values specific to the Turkish community as well as the medical literature as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism analysis for the SOD1 A251G region was done by PCR-RFLP method described by Silig et al, 2017 with minor modifications. Reaction mixture (25 L) consisted of 1 L of genomic DNA template (~100 ng/ L), 0.5 l of each forward and reverse primers (25pmol), 0.5 L of dNTPs (200 M), 2.5 L PCR buffer with 15 m M/L MgCl 2 (1x), 0.5 L of Taq polymerase (3 U/l) and 19.5 L nuclease MONIKA RANI ET AL S281 free water (Bangalore Genei, Bangalore, India) and 5% dimethyl sulfoxide.…”
Section: Sod1 Genotypingmentioning
confidence: 99%